A Review on Assessing Extent of Malware Damage and Basic Countermeasures - Omkar Mandar Pradhan; Harshita Kansara; Durvankur Sanjay Balkawade; Navnath Shete (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
In today's era of a digital world, Malware is a threat that looms above our heads. Attackers find a way to infect our systems to access our data and possibly disrupt our lives. Malware comes in many different forms and factors. The Malware could be harmful or a simple inconvenience, and it could cause a system-wide breakdown or even attempt to set up a backdoor. We chose the topic to get hands-on experience on at least some kinds of feasibly accessible Malwares. Learning about different Malware and testing a few of them out was a great way of understanding them clearly. In this research paper, We will be discussing kinds of Malware, their possible impacts, and some countermeasures. As Important as countermeasures against Malware is, understanding different types of malware threats is just as important. We will be testing some malware threats in a virtual environment using two different virtual machines configured to be vulnerable enough to get a good look at the damage done. We are using virtual environments supporting snapshots to revert the system to a working state if some malware affects it a way that leaves it unusable. We tested Malware that can establish a reverse TCP connection to give the attacker access to the system. We also tried some minor malware, which can kill random processes, delete arbitrary files, copy the largest files, mess with extensions, mess with environment variables and insert keyloggers.